The Importance of Civic Education in Building National Character for the Young Generation as Agents of Change - Muhammad Ridwan (International Journal of Religion, Humanity and Cultural Heritage, 2025)
Civic education is incorporated into every level of basic education as part of the curriculum and continuous teaching to fulfill national education goals. It aims to shape citizens who can actively contribute to sustainable development in a competitive country. The goal of civic education is to produce good citizens, capable of engaging in nation-building. One key aspect of this is character building, which is inseparable from the moral development needed in a civil society. As agents of change, the younger generation must be equipped with critical thinking skills to address both domestic and global issues that impact Indonesia. This study seeks to explore the role of civic education in helping future generations develop these skills and become responsible citizens capable of addressing concerns within and outside the country. The method used in this research is a literature review, which gathers data from books, documents, articles, and other publications related to evaluation issues in civic education. This approach is recommended for Indonesian students' education as it provides a deeper understanding of civic education's role in developing critical thinking. The findings of this study highlight that civic education not only shapes students into active and responsible citizens but also equips them with the tools to engage with national and global issues. It underscores the importance of integrating character and moral development into civic education to help create individuals who are prepared to lead and drive positive societal change.